Effect of experimental parameters on alginate/chitosan microparticles for BCG encapsulation - Caetano, Liliana Aranha (2016)
The aim of the present study was to develop novel Mycobacterium bovis bacille Calmette-Guérin (BCG)-loaded polymeric microparticles with optimized particle surface characteristics and biocompatibility, so that whole live attenuated bacteria could be further used for pre-exposure vaccination against Mycobacterium tuberculosis by the intranasal route. BCG was encapsulated in chitosan and alginate microparticles through three different polyionic complexation methods by high speed stirring. For comparison purposes, similar formulations were prepared with high shear homogenization and sonication. Additional optimization studies were conducted with polymers of different quality specifications in a wide range of pH values, and with three different cryoprotectors. Particle morphology, size distribution, encapsulation efficiency, surface charge, physicochemical properties and biocompatibility were assessed. Particles exhibited a micrometer size and a spherical morphology. Chitosan addition to BCG shifted the bacilli surface charge from negative zeta potential values to strongly positive ones. Chitosan of low molecular weight produced particle suspensions of lower size distribution and higher stability, allowing efficient BCG encapsulation and biocompatibility. Particle formulation consistency was improved when the availability of functional groups from alginate and chitosan was close to stoichiometric proportion. Thus, the herein described microparticulate system constitutes a promising strategy to deliver BCG vaccine by the intranasal route.